The effectiveness of electronic library service management at centra library in Yogyakarta State University - Salisa Roysri (JOURNAL OF EDUCATION, 2010)
This study was aimed at evaluating the effectiveness of electronic library service management concerning the components of (1) Input based on the items of the Mission Vision formulation, compilation of electronic programs and the availability of resources and (2) Process, including Planning, Organizing, Actuating and Controlling. The evaluation engaged a combined quantitative and qualitative paradigm in which three data collection techniques were used: a questionnaire, an interview, and an observation. The result from the questionnaire indicates that the mean of Input management is 3.16 which is the most effective performance and the mean score of Process is 3.32 which is also the most effective performance. The results of the interview and observation show that the management and leadership in the Electronic Section were formulated and implemented well since the mission and vision were disseminated and nearly everyone understood